Achilles tendon pain in male professional football players - A prospective five-season study of 88 injuries from the UEFA elite club injury study - Waldén, M.; Gajhede Knudsen, M.; Ekstrand, J.; Hägglund, M.; D`Hooghe, P.; Alfredson, H.; Bengtsson, H. (Open Access Journal of Sports Medicine, 2024)
Purpose: The objective was to describe the location, examination procedures, diagnoses, and treatment for gradual-onset Achilles tendon pain in male professional football (soccer) players.